A Medical Informatics Distance-learning Course for Latin America - Otero, P.; Hersh, W.; Luna, D.; González Bernaldo de Quirós, F. (Methods of Information in Medicine, 2010)
Background: There is a growing need and interest worldwide for healthcare and information technology professionals trained in medical informatics. Distance learning technologies are increasingly used to deliver such education, but have mainly been limited to the English language.Objective: Describe the implementation and student satisfaction of a medical informatics course delivered in Spanish for a Latin American audience.Methods: The course was based on the 10 x 10 program of the American Medical Informatics Association and Oregon Health & Science University that was translated and adapted to the Latin American setting. The initial course consisted of ten one-week units, currently the course has 15 modules that are delivered in 16 weeks with topics that address the needs of medical informatics in the region. We also administered an anonymous questionnaire of student satisfaction.Results: A total of 499 individuals have enrolled in the course, and 70% have completed it. Most of the students have been healthcare professionals (86%), with the largest proportion from Argentina. Student satisfaction with all aspects of the course was high. After the initial experience and feedback from the students, the course has been adapted to better meet regional needs.Conclusion: The initial experience obtained in training healthcare professionals in medical informatics in Latin America in their own language demonstrated that it could be used across the region, and this could represent a model for disseminating knowledge of medical informatics across other languages and cultures.
Keywords: Medical informatics /education; distance learning /methodology; teaching